2020
DOI: 10.15537/smj.2020.12.25570
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an Education-Based Intervention Program (EBIP) on dyspnea and chronic self-care management among chronic obstructive pulmonary disease patients

Abstract: To evaluate the impact of dyspnea and chronic self-care management outcomes of an Education-Based Intervention Program (EBIP) compared to routine care. Methods: The population of the study consisted of self-care management scale of 61 patients diagnosed with chronic obstructive pulmonary disease (COPD) stage 2 and within one month after discharge. A total of 51 conforming patients were divided into experimental and control groups for a single-blind randomized trial. Data were collected using an introductory in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 32 publications
0
20
0
1
Order By: Relevance
“…This result come in accordance with van de Hei et al, (2021) who studied ''Personalized medication adherence management in asthma and chronic obstructive pulmonary disease: a review of effective interventions and development of a practical adherence toolkit'' and reported that there were a positive correlation between the studied sample knowledge and their compliance to self-care management. Also this result was supported by Çevirme & Gökçay, (2020) who reported that the patients' self-care management was affected by the patients' level of knowledge.…”
Section: Discussionmentioning
confidence: 59%
“…This result come in accordance with van de Hei et al, (2021) who studied ''Personalized medication adherence management in asthma and chronic obstructive pulmonary disease: a review of effective interventions and development of a practical adherence toolkit'' and reported that there were a positive correlation between the studied sample knowledge and their compliance to self-care management. Also this result was supported by Çevirme & Gökçay, (2020) who reported that the patients' self-care management was affected by the patients' level of knowledge.…”
Section: Discussionmentioning
confidence: 59%
“…4,23,27,29,38,40,63,65,69 This was reflected in the definitions used by the authors of included texts that espoused a medicocentric conceptualisation of COPD self-management (notably, 16 texts did not present a formal definition of self-management). 23,27,32,34,37,41,45,46,48,52,54,58,59,61 Many of the authors referred to medical aspects in the definitions they used, including symptom management, self-monitoring, compliance with medical regimens and self-management interventions, and with the recommendations of health care professionals. 24,26,29,31,35,36,38,39,42,43,49,50,55,57,60,62,68 The concepts of patient education and behaviour change were also included in the definitions used by authors.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, within the main body of the medicocentric texts, emphasis was placed on the treatment of COPD, carrying out disease-specific medical regimens, managing symptoms, and adherence to treatment regimens. 23,25,28,30,32,33,35,39,43,44,47,49,50,52,59,61,63,66,69 There was a strong focus on education of people with COPD. 23,29,31,35,37,41,43,44,46,52,54,57,62,65 Many of the publications that took a medicocentric perspective also emphasised the role of lifestyle and behaviour change.…”
Section: Resultsmentioning
confidence: 99%
“…Our study showed that patients with more access to medical resources are more likely to be on a positive trajectory. Some studies also have demonstrated that self‐care programmes can improve patients' self‐care ability and self‐care efficacy (Cevirme & Gokcay, 2020; Liou et al, 2020). However, the follow‐up duration of these studies was only followed up for 3 months for patients, and the short‐term effect was good but the long‐term effect was unknown.…”
Section: Discussionmentioning
confidence: 99%